Gastrointestinal bleeding during acute ischaemic stroke hospitalisation increases the risk of stroke recurrence - Du, Wanliang (Stroke Vasc Neurol, 2020)
OBJECTIVE: Gastrointestinal (GI) bleeding in patients who had a stroke is strongly associated with a higher risk of death and loss of independence. However, it is unknown whether GI bleeding increases risk for recurrence of stroke. In this study, we assess the potential relationship between GI bleeding and stroke recurrence in patients within 12 months of an acute ischaemic stroke (AIS), using the China National Stroke Registry (CNSR). METHODS: This study included 22 216 patients who had an ischaemic stroke included in the CNSR from 2007 to 2008. We analysed baseline patient characteristics, GI bleeding and outcomes of patients who had an AIS, specifically stroke recurrence at 3, 6 and 12 months. We used multivariable logistic regression to evaluate a possible association between GI bleeding and stroke recurrence. RESULTS: Of the 12 415 patients included in our study, 12.3%, 15.5% and 17.7% had a stroke recurrence at 3, 6 and 12 months, respectively. GI bleeding was an independent stroke recurrence risk factor in patients after ischaemic stroke at 3 months (adjusted OR 1.481, 95% CI 1.118 to 1.962), 6 months (adjusted OR 1.448, 95% CI 1.106 to 1.896) and 12 months (adjusted OR 1.350; 95% CI 1.034 to 1.763). CONCLUSION: GI bleeding was associated with the increased risk of stroke recurrence after an AIS.